Biological and therapeutic role of LSD1 in Alzheimer’s diseases - Li, Yu; Zhao, Yuanyuan; Li, Xiaona; Zhai, Liuqun; Zheng, Hua; Yan, Ying; Fu, Qiang; Ma, Jinlian; Fu, Haier; Zhang, Zhenqiang; Li, Zhonghua (Frontiers in Pharmacology, 2022)
Alzheimer’s disease (AD) is a common chronic neurodegenerative disease characterized by cognitive learning and memory impairments, however, current treatments only provide symptomatic relief. Lysine-specific demethylase 1 (LSD1), regulating the homeostasis of histone methylation, plays an important role in the pathogenesis of many neurodegenerative disorders. LSD1 functions in regulating gene expression via transcriptional repression or activation, and is involved in initiation and progression of AD. Pharmacological inhibition of LSD1 has shown promising therapeutic benefits for AD treatment. In this review, we attempt to elaborate on the role of LSD1 in some aspects of AD including neuroinflammation, autophagy, neurotransmitters, ferroptosis, tau protein, as well as LSD1 inhibitors under clinical assessments for AD treatment.